2011
DOI: 10.1002/pros.21333
|View full text |Cite
|
Sign up to set email alerts
|

Prostate‐derived Ets transcription factor (PDEF) is a potential prognostic marker in patients with prostate cancer

Abstract: Background Reduced expression of prostate-derived Ets transcription factor (PDEF) leads to morphologic change as well as increased migration and invasiveness of prostate cancer cells. However, the clinical relevance of PDEF expression and its relationship to anti-apoptotic protein survivin is yet to be determined. Methods Tissue microarrays of 73 prostate carcinomas and their adjacent benign prostate tissue, as well as 50 benign prostates were evaluated for PDEF expression by immunohistochemistry. Results we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
40
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 26 publications
8
40
2
Order By: Relevance
“…We also demonstrated that there is an inverse relationship between SPDEF expression and MMP9 expression in the clinical samples in tissue microarray having both normal and cancerous tumor samples of prostate cancer (10). Our results demonstrat-ing the loss of SPDEF and aggressive prostate cancer have been confirmed by at least two other independent studies (11,12); one follow-up study in fact suggests that loss of SPDEF could be a predictor not only of aggressive prostate cancer but also of prostate cancer-associated death (12). Taken together, these studies clearly provide compelling evidence of the association between loss of SPDEF and aggressive prostate cancer.…”
supporting
confidence: 81%
“…We also demonstrated that there is an inverse relationship between SPDEF expression and MMP9 expression in the clinical samples in tissue microarray having both normal and cancerous tumor samples of prostate cancer (10). Our results demonstrat-ing the loss of SPDEF and aggressive prostate cancer have been confirmed by at least two other independent studies (11,12); one follow-up study in fact suggests that loss of SPDEF could be a predictor not only of aggressive prostate cancer but also of prostate cancer-associated death (12). Taken together, these studies clearly provide compelling evidence of the association between loss of SPDEF and aggressive prostate cancer.…”
supporting
confidence: 81%
“…Our findings, that SPDEF expression limits the ability of prostate tumor cells to survive in the circulation and thereby establish metastases, are concordant with studies showing that SPDEF protein expression is decreased or undetectable in a majority of advanced/metastatic human prostate tumors (12,14), suggesting that the loss of SPDEF may in part contribute to prostate tumor metastasis, at least in subsets of patients. This would explain the positive correlation between the loss of SPDEF expression in clinical specimens of prostate cancer and cancer specific death in these patients, as observed recently (15). Our exciting results suggest that SPDEF may represent a modifiable therapeutic target to prevent or decrease tumor cell survival or growth at secondary sites in prostate cancer and perhaps other malignancies.…”
Section: Discussionsupporting
confidence: 77%
“…These studies also suggested that SPDEF expression suppressed an aggressive phenotype in prostate cancer. Our findings are in contrast to a report by Sood et al (13) but have been confirmed and even extended by two additional groups (14,15). In fact, Ghadersohi et al (15) associated SPDEF expression with a favorable prognosis in localized prostate cancer.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…In advanced prostate cancer and prostate cancer-derived cell lines, SPDEF was either decreased or lost [23], [34]. It was also shown that SPDEF expression is decreased during the transition from low-grade to high-grade prostate cancer [23], [34], [35]. Two studies had shown correlation between decreased expression of SPDEF and poor prognosis in prostate cancer [23], [35].…”
Section: Discussionmentioning
confidence: 99%